Care of Patients with Huntington S Disease in South America: A Survey [Cuidado de Pacientes Com Doença de Huntington Na América Do Sul: Um Inquérito] - Chana-Cuevas, P (2013)
Huntington s disease (HD) is a rare neurodegenerative disease with a multitude of symptoms, which requires access to specialized multidisciplinary care for adequate management. The aim of this study was to survey the characteristics of care in various HD centers in South America (SA). Methods: A questionnaire was sent to 24 centers involved in the care for HD patients in SA. Results: Of the total 24 centers, 19 (79.2%) are academic units. The majority of centers (62.5%) are general movement disorders clinics. Multidisciplinary care is available in 19 (79.2%) centers and in 20 (83.3%) care is provided free of charge. Genetic testing and counseling are available in 25 and 66.6% of centers, respectively. The majority of centers (83.3%) have no institutional support for end-stage care. Conclusions: Although HD centers in SA are committed to providing multidisciplinary care, access to genetic counseling and end-stage care are lacking in most centers.